Who lives in the c-suite? Organizational structure and the division of labor in top management - Maria Guadalupe; Hongyi Li; Julie M. Wulf (Institute for the Study of Labor (IZA), 2012)
This paper shows that top management structures in large US firms radically changed since the mid-1980s. While the number of managers reporting directly to the CEO doubled, the growth was driven primarily by functional managers rather than general managers. Using panel data on senior management positions, we explore the relationship between changes in executive team composition, firm diversification, and IT investments - which arguably alter returns to exploiting synergies through corporate-wide coordination by functional managers in headquarters. We find that the number of functional managers closer to the product (product functions i.e., marketing, R&D) increase as firms focus their businesses, while the number of functional managers farther from the product (administrative functions i.e., finance, law, HR) increase with IT investments. Finally, we show that general manager pay decreases as functional managers join the executive team suggesting a shift in activities from general to functional managers - a phenomenon we term functional centralization.
Keywords: J24; J33; L25; D22; 330; communication; organizational design; functions; centralization; M-form; hierarchy; top management team; information technology; activities; diversification; Führungskräfte; Arbeitsgruppe; Arbeitsorganisation; Organisationsstruktur; Diversifikation; Betriebliche Investitionspolitik; Informationstechnik; USA